Use of a Mindfulness Smartphone App in an Advanced Psychiatry Elective for Pharmacy Students - Jerry McGuire; Teresa Zhen (University of Minnesota Libraries Publishing, 2019)
Background: There is a mental health crisis among US University students. Evidence supporting techniques to help students manage the stress are critically needed. Mindfulness meditation is one such strategy which may be helpful for pharmacy students. Innovation: Third-year pharmacy students enrolled in an Advanced Psychiatry elective course were invited to participate in the study. Students were given a 10-day assignment to participate in 10 free mindfulness sessions offered by the smart phone app, Headspace®. The Mindful Attention Awareness Scale (MAAS) was completed before and after the assignment. Student qualitative feedback was also obtained after utilization of the app. Findings: Seventy-six percent of students completed the mindfulness sessions daily. A small, non-statistically significant change in MAAS Total Score was observed in the students after use of the mindfulness app. The majority of students would recommend the mindfulness app to their patients, as well as 1st year pharmacy students. The students also reported that the assignment aided in their education about non-pharmacologic treatment options for depression and anxiety. Conclusion: This pilot study provides preliminary evidence for the further investigation of mindfulness meditation smartphone apps       in pharmacy students both as a tool to aid in managing the stress of pharmacy school and as a teaching tool.   Article Type: Note